Assessing Fluoride Impact in Phosphogypsum: Strength and Leaching Behavior of Cemented Paste Backfill - Qinli Zhang; Yikun Yang; Daolin Wang; Bin Liu; Yan Feng; Zian Song; Qiusong Chen (Applied Sciences)
Phosphogypsum (PG)-based cemented paste backfill (PCPB) is a widely used method for the large-scale disposal of phosphoric acid waste. However, fluoride contaminants in PG pose a significant risk of groundwater pollution. Effective pretreatment methods have been developed to mitigate this issue, but there is limited research on the specific pretreatment standards needed to control fluoride leaching. This study investigates the impact of initial fluoride content (IFC) in PG samples on the strength and leaching behavior of PCPB to establish appropriate pretreatment standards. Pure CaSO4·2H2O and NaF were used to simulate PG samples with varying IFC levels. The findings indicate that lower IFC leads to stronger PCPBs after 28 days of curing. To ensure compliance with Chinese national standards, the initial fluoride concentration must be below 0.0093 wt% to prevent excessive leaching. Microlevel analyses reveal that fluoride influences the hydration reactions of C2S and C3S in cement, affecting the formation of C-S-H and Ca(OH)2. Fluoride is primarily immobilized in PCPB as CaF2, which can either form gypsum crystals within the complex structure or be adsorbed onto hydration products. This research provides crucial insights into the pretreatment standards required for controlling fluoride leaching, offering a foundation for the industrial application of PG.